The fear index [compact disc, unabridged] - Harris, Robert, 1957- (Random House, 2011)
Dr. Max Hoffman is a legend. A physicist once employed on the Large Hadron Collider, he now uses a revolutionary and highly secret system of computer algorithms to trade on the world's financial markets. None of his rivals is sure how he does it, but somehow Hoffman's hedge fund - built around the standard measure of market volatility: the VIX or 'Fear Index' - generates astonishing returns for his investors. But now someone is trying to destroy him.